THE CPA EXAMINATION. - Newcomer, Hale L. (The Accounting Review, 1949)
In January 1947, the Board of Examiners of the American Institute of Accountants requested the appointment of a committee of the American Accounting Association to survey the board's examination procedures, the content of the Uniform CPA examinations, timings, weightings, grading, and any other items, which the committee deemed pertinent. Such a committee has been functioning the past year. The committee is not yet in a position to render a formal report, and the remarks and opinions in this paper should not be considered necessarily representative of committee consensus. Nevertheless, the speaker has not hesitated to draw upon the ideas and research of members of the Committee on the Uniform CPA Examination or on the ideas and research of others. Examiners have a tremendous obligation and responsibility to the profession, the states and territories delegating duties to them, and to the candidate. The approach of the examiners should be objective; it is their responsibility to determine the standards set by examination and grading. Educators may help in construction and arrayal of data, timing, weighting, and suggestions as to grading procedures and techniques.